Chemical characteristics of two strawberry cultivars and sensory analysis of fruits - Rustich, Alexandro Oldair; Coutinho, Pablo Wenderson Ribeiro; Dalastra, Graciela Maiara; Albano, Karine; Souza, Eduarda Yasmin Nunes de (Scientia Agraria Paranaensis, 2023)
Strawberry cultivation is of great economic importance to family farming. For this reason, studies and experiments have been carried out to improve management and increase the productivity of this fruit. The aim of this study was to evaluate the characteristics of the fruit's chemical qualities and sensory analysis between two strawberry cultivars, Pircinque and VR10. The strawberries used in the research were grown on a property in Serranópolis do Iguaçu, PR, in a protected environment. The plants were planted on top of white mulch using the traditional planting method. Chemical properties such as soluble solids(oBrix), pH, AT (% citric acid), RATIO (soluble solids/titratable acidity) were evaluated. In addition, a sensory analysis was carried out, inviting 20 untrained tasters of both sexes and different ages from the Uniguaçu educational institution. The design used was completely randomized (DIC), with two strawberry cultivars Pircinque and VR10. Based on the chemical and sensory analyses carried out, the Pircinque strawberry cultivar stood out when compared to the VR10 cultivar, within the parameters and criteria evaluated. Standing out in all the parameters analyzed, the Pircinque cultivar is the best option when compared to the VR10 variety in terms of taste and quality.